1996
DOI: 10.1046/j.1460-9592.1996.d01-24.x
|View full text |Cite
|
Sign up to set email alerts
|

The rectus sheath block in paediatric anaesthesia: new indications for an old technique?

Abstract: The rectus sheath block has been used with success for postoperative analgesia in adults. This paper reviews the anatomy of the rectus sheath, and presents our initial experience of using the block to provide intra- and postoperative analgesia in children having repair of umbilical and paraumbilical hernia. The rectus sheath block appears to be a useful technique in children, particularly for paediatric day-cases surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 0 publications
1
77
0
3
Order By: Relevance
“…RS block has been assessed as a modality for pain management in umbilical hernia repair. 12,14,15 Isaac et al 14 compared RS block with local anesthetic infiltration and found no difference in postoperative opioid use and pain scores between the two modalities. However, similar to our study, Gurnaney et al 12 found that ultrasound-guided RS block provided better analgesia than local anesthetic infiltration in umbilical hernia repair cases; furthermore, it can provide real-time information on the needle tip location and the local anesthetic delivery to the desired location.…”
Section: Discussionmentioning
confidence: 99%
“…RS block has been assessed as a modality for pain management in umbilical hernia repair. 12,14,15 Isaac et al 14 compared RS block with local anesthetic infiltration and found no difference in postoperative opioid use and pain scores between the two modalities. However, similar to our study, Gurnaney et al 12 found that ultrasound-guided RS block provided better analgesia than local anesthetic infiltration in umbilical hernia repair cases; furthermore, it can provide real-time information on the needle tip location and the local anesthetic delivery to the desired location.…”
Section: Discussionmentioning
confidence: 99%
“…In 1996, it was suggested that this old technique might provide analgesia following umbilical hernia repairs in children [54]. …”
Section: Clinical Background and Anatomymentioning
confidence: 99%
“…a grade A recommendation for the use of US guidance for the RS block has been granted (Abrahams 2010). The RS block has been utilized to provide analgesia for midline incisions and laparoscopic procedures (Ferguson 1996, Abrahams 2010. RS blocks may also be effective in reducing postoperative pain in upper abdominal surgery as an alternative method to epidural analgesia in anticoagulated patients (Osaka 2010).…”
Section: Usg Rectus Sheath (Rs) Blockmentioning
confidence: 99%